How instructor-developed screencasts benefit college students’ learning of maths: insights from an Irish case study - Tunku Ahmad, Tunku Badariah; Doheny, Frank; Faherty, Sheila; Harding, Nuala (Universiti Malaya, 2013)

(untitled)
This qualitative case study explored how students learning Maths at an Irish institute of higher education benefited from their instructor’s use of self-developed screencasts. The screencasts (47 in total) were posted on the institute’s Maths Moodle site for students to access. One hundred and thirty-eight (n = 138) students participated in an online open-response survey. Students’ commentary was analyzed using thematic content analysis (TCA). Themes that represented different types of screencast benefit to students were generated from the data. Consistent with previous studies, the findings show that a vast majority of students (88.4%) used the screencasts for many different purposes and viewed the videos as an extremely useful tool that enhanced their Maths learning experience. Ten primary benefits of screencasts emerged, namely allowing flexible and personalized learning, supplementing lectures and enhancing understanding of Maths keyskills, facilitating exam revision and material review, providing multimodal support for Maths learning, helping students to keep track with the Maths modules, providing a tighter match with course content, delivering a vicarious learning experience, serving as a memory aid, filling in gaps in class notes, and making Maths more enjoyable. The findings support the use of screencasts in facilitating and enhancing students’ learning of Maths in higher education.